Determinant Factors for Learning Model Development: Their Influence on Employee Performance - Erwin, Yulianto; Deden, Abdul Wahab Sya’roni; Neneng, Hayati; Yudi Wahyudin, Suwandi; Rida, Hardianti (INTI International University, 2024)
Business competition and high demands for services in the banking industry currently require companies to have increasingly high organizational capacity that relies on human resource performance and learning models. This research aims to identify, study, and analyze Learning Models to Improve the Performance of Banking Industry Employees. The purpose of this study is to identify, investigate, and evaluate the factors that will be incorporated into the learning model and how they affect worker performance. A Systematic Literature Review (SLR) is the research method approach that is employed. It is completed by finding pertinent research, evaluating its caliber, and producing a scientific summary of the findings of the earlier study. Research talks yielded variables that will be used as learning models to enhance worker performance. A human resource management method is used in this study, particularly when examining the variables that affect employee performance. It was discovered that five variables—three independents, one intervening, and one dependent—were employed as research items in this study. To increase employee performance, the learning management system, learning instructional design, learning assessment, and competency development were implemented. What makes the ensuing research unusual is that no learning model emerged from these processes.